Nanoscale pores plus precipitates rendering high-performance thermoelectric SnTe1-xSex with refined band structures. (June 2019) - Hong, Min; Wang, Yuan; Xu, Shengduo; Shi, Xun; Chen, Lidong; Zou, Jin; Chen, Zhi-Gang
Abstract: Thermoelectric performance is proportional to the thermal conductivity reciprocal and power-factor, which are impacted by microstructures and electronic band structures, respectively. Herein, we study the effect of nanoscale pores on thermal conductivity. Within Cd-doped SnTe1-x Sex, electron microscopy characterizations indicate the majority of pores are less than 200 nm, which is comparable to the phonon mean free path. Together with the point defects and nanoprecipitates, an ultra-low lattice thermal conductivity is obtained. Electrically, we find that the slight overdose of cation lone pair s 2 character at L point of the first Brillion zone yields the energetically higher valence band edge at L point than at Σ point in rock-salt chalcogenides. As for SnTe1-x Sex, Cd is a dopant free of lone pair s 2 orbital. Cd doping decreases the energy offset of multivalence bands for SnTe1-x Sex by partially reducing the cation lone pair s 2 character. The refined band structures yield an enhanced power-factor. Combined with the decreased thermal conductivity, a figure-of-merit > 1.5 has been obtained. The demonstrated strategies of exploring nanoscale pores with size matching phonon mean free path to decrease lattice thermal conductivity and the computationally screening suitable dopants to modify band structures can enlighten the development of high-performance thermoelectric candidates in wide materials. Graphical abstract: Image 1 Highlights: Nanoscale pores with sizes matching phonon mean free path decrease the thermal conductivity. The refined band structures lead to enhanced power-factor. Dual valence band edges in rock-salt chalcogenides are ascribed to the weak contribution of cation lone pair s 2 orbital. Exploring the nanoscale pores extends the nanostructuring strategy for enhancing thermoelectric performance.